Reducing complications in liposuction - Luiz Felipe Duarte Fernandes Vieira; Carlos Lacerda Andrade Almeida; João Paulo Silva Siqueira; Adriano Souza Costa; Leonardo Campello Almeida (Revista Brasileira de Cirurgia Plástica, 2024)
Introduction: Liposuction is the most commonly performed cosmetic surgical procedure, with the main complication being blood loss resulting from the procedure, which can lead to life-threatening situations. Method: This study evaluated the use of Medtronic's autoLog® equipment in the recovery of red blood cells from the infranatant liposuction in 10 patients. Results: The results demonstrated a significant reduction in the drop in hematocrit and hemoglobin levels in the postoperative period of patients when compared with the existing literature. Conclusion: The use of such equipment contributes to the prevention of complications, as well as allowing patients with restrictions on undergoing liposuction, such as those with chronic anemia, to be eligible for liposuction.